Basal Core Promoter and Precore Mutations in the Hepatitis B Virus Genome Enhance Replication Efficacy of Lamivudine-Resistant Mutants - Frank Tacke; Christina Gehrke; Tom Luedde; Albert Heim; Michael P. Manns; Christian Trautwein (2004)
ABSTRACT During chronic hepatitis B virus (HBV) infection, mutations in the precore (PC) or basal core promoter (BCP) region affecting HBV e antigen (HBeAg) expression occur commonly and represent the predominant virus species in patients with HBeAg-negative chronic hepatitis B. The PC mutation (G1896A+C1858T) creates a translational stop codon resulting in absent HBeAg expression, whereas BCP mutations (A1762T/G1764A) reduce HBeAg expression by transcriptional mechanisms. Treatment of chronic HBV infection with lamivudine (LMV) often selects drug-resistant strains with single (rtM204I) or double (rtL180M+rtM204V) point mutations in the YMDD motif of HBV reverse transcriptase. We cloned replication-competent HBV vectors (genotype A, adw2) combining mutations in the core (wild type [wt], PC, and BCP) and polymerase gene (wt, rtM204I, and rtL180M/M204V) and analyzed virus replication and drug sensitivity in vitro. Resistance to LMV (rtM204I/rtL180M+rtM204V) was accompanied by a reduced replication efficacy as evidenced by reduced pregenomic RNA, encapsidated progeny DNA, polymerase activity, and virion release. PC mutations alone did not alter virus replication but restored replication efficacy of the LMV-resistant mutants without affecting drug resistance. BCP mutants had higher replication capacities than did the wt, also in combination with LMV resistance mutations. All nine HBV constructs showed similar sensitivities to adefovir. In conclusion, BCP-PC mutations directly impact the replication capacity of LMV-resistant mutants. PC mutations compensated for replication inefficiency of LMV-resistant mutants, whereas BCP mutations increased viral replication levels to above the wt baseline values, even in LMV-resistant mutants, without affecting drug sensitivity in vitro. Adefovir may be an effective treatment when combinations of core and polymerase mutations occur.